2015
DOI: 10.1002/bio.2901
|View full text |Cite
|
Sign up to set email alerts
|

A very simple high‐performance liquid chromatographic method with fluorescence detection for the determination of gemifloxacin in human breast milk

Abstract: A high-performance liquid chromatographic method with fluorescence detection was developed and validated for the determination of gemifloxacin in human breast milk. The proposed method allows the determination of gemifloxacin in breast milk samples without complex sample preparation. The samples were mixed with a mobile phase and filtered with a 0.45 µm polytetrafluoroethylene filter before analysis. Chromatographic separation was carried out on a C18 column (150 × 4.6 mm, 5 µm I.D.) using methanol:50 mM ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Water was purified by an aquaMAXTMultra system (Younglin Instruments, Anyang, Korea). In the literature there are several methods for the quantitation of GMX in human plasma [5][6][7][8][9] and one method in breast milk [10]. In order to separate the anayte from proteins, lipids and other matrix constituents solid-phase extraction (SPE), liquid-liquid extraction (LLE), protein precipitation techniques were used in these studies.…”
Section: Apparatusmentioning
confidence: 99%
“…Water was purified by an aquaMAXTMultra system (Younglin Instruments, Anyang, Korea). In the literature there are several methods for the quantitation of GMX in human plasma [5][6][7][8][9] and one method in breast milk [10]. In order to separate the anayte from proteins, lipids and other matrix constituents solid-phase extraction (SPE), liquid-liquid extraction (LLE), protein precipitation techniques were used in these studies.…”
Section: Apparatusmentioning
confidence: 99%
“…According to a literature review, analytical methods used for the determination of gemifloxacin include spectrophotometry [ 6 , 7 , 8 ], spectrofluorometry [ 9 , 10 ], polarography [ 11 ], voltammetry [ 12 , 13 , 14 ], HP-TLC [ 15 , 16 ], HPLC-UV [ 17 , 18 , 19 ] , HPLC-F [ 20 , 21 , 22 ], HPLC-MS [ 23 , 24 , 25 ], and potentiometry [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical methods were also reported for the determination of quinolones [13,14]. The reported HPTLC methods included the determination of MX in tablets [15], MX with other fluoroquinolone antibiotics in industrial wastewater [16], LV with ornidazole or cefpodoxime [17,18] and GM [19,20]; the reported HPLC methods involved the determination of MX [21][22][23], LV [24,25], MX by stability studies [26], LV in urine [27], and GM in pharmaceutical and biological matrices [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%